An Empirical Investigation on Brick and Mortar Attributes for the Effective Adaptation of Online Banking in Pakistan - Yumna Ashraf; Malik Shahzad Shabbir (UW Journal of Management Sciences, 2022)
Purpose: The study intended to analyze the impact of Brick and Mortar trustworthiness attributes along the social demographic traits which effects the customer’s perception to effectively adopt online banking services. Trust is one of the biggest challenges for the consolidation of online banking in the future. Thus Brickand- mortar trustworthiness forms an intangible active, which may create a competitive advantage for the banks. Design/Methodology: The study used self-administrative questionnaire to collect the data from the customers of both the Islamic and conventional banks in Rawalpindi and Islamabad. Multiple linear regression technique was used to analyze the impact of brick and mortar trustworthiness attributes (honesty, benevolence and competence) and social demographic factors (gender, education, age and income). Findings: The results of the study showed that the Brick and Mortar trustworthiness attributes have positive and significant impact on the adaptation of the online banking services, however the higher level of education inversely impacts the adaptation of the online banking service. Practical Implication: This paper highlights the significance of trustworthiness for influencing the perception of the consumers to adopt the online banking services. The result of the study shows that there is a need to target marketing actions on certain segments of the population. Implications: This paper offers an innovative approach to analyze the Brick and Mortar trustworthiness attributes with the socio demographic factors to influence the consumers’ perceptions. This analysis perspective has not been previously used in the literature of developing countries.